System analysis of the North Atlantic air traffic complex; final report, December 1962, Research Division project no. 116-9R. - Arcon Corporation.; United States. Federal Aviation Agency. Systems Research and Development Service. (Lexington, 1963)
"Prepared . for the Systems Research and Development Service, Federal Aviation Agency, under contract no. FAA/BRD-334." "R62-3." Mode of access: Internet.